Design And Development Of Active Power Filter For Harmonic Minimization Using Synchronous Reference Frame (SRF) - Omar, Rosli; Al-Hiealy, Mohammed Rasheed Jubair; Low, Zheng Kai; Sulaiman, Marizan (Asian Research Publishing Network (ARPN), 2019)
The research for the aimed towards avoiding the waveform of the current from distorted is make the researchers interested to do that.. The controllers used in an active power filter play an important role in determining the current waveform in electrical system will smooth with a minimum of the total harmonic distortion (THD). The main purpose of this paper is to propose the controller of an active power filter based on synchronous reference frame (SRF). A model of the proposed controller has been developed using MATLAB/SIMULINK. The results of the simulation shows that the effectiveness of the proposed controller toward in reducing THD at the acceptable.